Mobility for learners and staff – higher education students and staff mobility inter-institutional agreement 2017-2021 between programme countries - Universidad de Murcia and Universidade Lusíada - Universidade Lusíada (2017)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme; - Erasmus subject area: Law; criminology.